The Role of K+ And Ca2+ Ion Channels in Α-Terpinyle Acetate-Induced Vasodilation in Rat’s Aortic Rings - Kheder, Dlzar A.; Al-Habib, Omar A. M.; Adam, Lina N. (Science Journal of University of Zakho, 2017)
The monoterpene, α-terpinyle acetate (TA) is a constituent of essential oils present in aromatic plants. Since the role of ion channels and endothelial hyperpolarizing factors in TA induced relaxation in rat’s aorta is unknown, the current study aimed to study the mechanism underlying the vasodilatory effect of TA in isolated aortic rings. Terpinyle acetate induced a potent vasodilation in rat aortic rings with a percentage of relaxation of 63.79 %. The results of the role of K+ channel subtypes in vasorelaxation revealed that both Kv and KATP played a major role since GLIB produced a maximum percent of inhibition in the relaxation produced by TA to 8.91 %; this was followed by 4-AP in which the percent of inhibition reduced to 14.95. On the other hand, Kir played no role in the TA induced vasorelaxation since BaCl2 did not produce any inhibition in aortic relaxation. Furthermore, also L-type Ca2+ channel played no role in TA induced relaxation since the L-type Ca2+ channel inhibitor Nifedipine did not reduce the percent of relaxation. Endothelium also played a considerable role in the induced vasorelaxation since, in denuded aorta, the percent of relaxation was reduced to 36%. Preincubation of the aortic ring with methylene blue, a soluble cGMP inhibitor also significantly reduced the TA induced relaxation to 16.39%. In contrast, preincubation with cyclooxygenase inhibitor Indomethacin did not produce any inhibitory effect on AT induced vasorelaxation. It can be concluded from these novel results that AT induced vasorelaxation involve the activation of KV, KATP channels and at least partly dependent on endothelium via the activation NO-cGMP signal transduction pathway.
Keywords: α-Terpinyle Acetate; K; L-type Ca2 channels; vasodilation; aorta; rats